Clinical Characteristics and Therapeutic Outcome of Carotid-Cavernous Fistula - Ressa Yuneta; M Sidik; Syntia Nusanti; Jacub Pandelaki (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2016)
Background: Carotid-cavernous fistula (CCF) is an abnormal communication between the carotid arterial system and the cavernous sinus. It can manifest as proptosis, bruit, corkscrew appearance or other signs. The aims of this study were to evaluate the clinical characteristics and result of CCF therapy.Methods: This is a retrospective study which evaluated the clinical characteristic, outcome of therapy and complications after embolization in CCF patient confirmed by digital subtraction angiography (DSA) from January 2012 to December 2014.Results: Twenty-three patients, 16 male and 7 female, were diagnosed as CCF. Mean age was 26Â±10.5 years old. The most common etiology was trauma (91.3%) with onset ranging from immediately to 17 months after trauma. The frequent ocular manifestations were proptosis, bruit, and conjunctival abnormalities. Other ocular signs were ophthalmoplegia, secondary glaucoma, abnormalities of posterior segment, and decrease of visual acuity. Seventy-eight percent patient was type A CCF. Fifteen patients underwent embolization, 3 patients couldnâ€™t be embolized then treated by manual carotid compression, 5 patients were still waiting for schedule of embolization. Clinical signs of 63% patients were improved in 1 week after embolization. After several months, 2 patients with carotid compression was improved and 1 patient had persistent signs. Complications of embolization include transient sensoric aphasia (1 pasien) and central retinal vein occlusion (2 patients).Conclusion: Clinical characteristics of CCF in this study were not different with previous descriptive studies and most cases showed improvement in clinical signs after therapy. Â Keywords: CCF, embolization